Rethinking Journalism Education in Indonesia: Nine Theses - Thomas Hanitzsch (MediaTor (Jurnal Komunikasi), 2001)
Since the number of Indonesian mass media products is rapidly increasing, the media industry is seeking – more than ever before – for qualified and professional journalists. Although Indonesia disposes of a broad variety in journalism education, the findings of a qualitative case study show a serious amount of problems and deficiencies. What the Indonesian journalism education currently needs, is a rethinking of political, legal, and curricula aspects within a nationwide debate.